DO DIREITO FUNDAMENTAL À PRIVACIDADE AO BIGDATA: DESAFIOS NA PROTEÇÃO AOS DADOS PESSOAIS E IMPACTOS À DEMOCRACIA NA ERA DIGITAL (Revista Paradigma, 2022)
The purpose of this article was to analyse the historical evolution of the right to privacy until its most modern formation: personal data. The research was based on the bibliographic type and the deductive method was used to initially explain the origin of privacy and its modifications. Then, we began to analyze the legislative changes and the legal constructions around them, as well as the ways to constitute an autonomous right. Finally, an attempt was made to demonstrate the impact and challenges for democracy in an era marked by intimacy intertwined with technology, which made it possible to conclude that the debate must always be based on the protection of information, which is the basic precept for guaranteeing this fundamental right, in addition to working in a legal system that provides limiting and transparent means of how data are processed.
Keywords: Personal data. Democracy; Privacy. Digital social networks.